Acute response of intermittent and continuous aerobic exercises on blood glucose of adolescents - Valderi Lima; Luis Mascarenhas; Juliana Decimo; William Souza; Suzana França; Neiva Leite (Revista Brasileira de Atividade Física e Saúde)
The purpose of the study was to investigate the acute effect of continuous and intermittent aerobic exercise on blood glucose of adolescents with type 1 diabetes. A cross-sectional analysis of eight adolescents with type 1 diabetes mellitus (10-15 years) was conducted, and variables such as body mass, height, body mass index z score, glycated hemoglobin and cardiorespiratory fitness were assessed. There were two tests on a cycle ergometer: 30 minutes of continuous exercise and 30 minutes of intermittent exercise. Blood glucose was measured before and after the exercises and lactate concentration was measured at the end of the exercise. Student’s t test and Pearson’s correlation were used, considering p<0.05. In the continuous exercise protocol, there was a significant difference in pre- and post-exercise blood glucose levels (p = 0.048), whereas the intermittent exercise protocol did not show statistically significant differences in blood glucose. Higher concentrations of lactate were found after the intermittent exercises (p = 0.036). There was a strong correlation between glycemic control and body mass index z score (r = 0.893 p = 0.041). Regarding the other variables, there were no significant correlations. The reduction in blood glucose was lower after intermittent aerobic exercises, compared with continuous exercises, which could be an interesting strategy to prevent acute exercise-induced hypoglycemia.